Therapeutic Targeting of SGLT2: A New Era in the Treatment of Diabetes and Diabetic Kidney Disease - Shaffner, James; Chen, Bohan; Malhotra, Deepak K.; Dworkin, Lance D.; Gong, Rujun (Frontiers in Endocrinology, 2021)
As the prevalence of diabetic kidney disease (DKD) continues to rise, so does the need for a novel therapeutic modality that can control and slow its progression to end-stage renal disease (ESRD). The advent of sodium-glucose cotransporter-2 (SGLT2) inhibitors has provided a major advancement for the treatment of DKD. However, there still remains insufficient understanding of the mechanism of action and effectiveness of this drug, and as a result, its use has been very limited. Burgeoning evidence suggests that the SGLT2 inhibitors possess renal protective activities that are able to lower glycemic levels, improve blood pressure/hemodynamics, cause body weight loss, mitigate oxidative stress, exert anti-inflammatory and anti-fibrotic effects, reduce urinary albumin excretion, lower uric acid levels, diminish the activity of intrarenal renin-angiotensin-aldosterone system, and reduce natriuretic peptide levels. SGLT2 inhibitors have been shown to be safe and beneficial for the use in patients with a GFR ≥30mL/min/1.73m2, associated with a constellation of signs of metabolic reprogramming, including enhanced ketogenesis, which may be responsible for the correction of metabolic reprogramming that underlies DKD. This article aims to provide a comprehensive overview and better understanding of the SGLT2 inhibitor and its benefits as it pertains to renal pathophysiology. It summarizes our recent understanding on the mechanisms of action of SGLT2 inhibitors, discusses the effects of SGLT2 inhibitors on diabetes and DKD, and presents future research directions and therapeutic potential.